Beauty and brutality Manila and its global discontents - Manalansan, Martin F. IV. 1960-; Diaz, Robert; Tolentino, Rolando B. (Temple University Press, 2023)
"This edited volume deconstructs popular generalizations of Manila. Bringing together scholars from across the humanities and social sciences, this volume presents a series of multidisciplinary lenses to understand the complexities and contradictions of Manila, illustrating the breadth of experience it represents and that its citizens live"--
Keywords: Manila (Philippines) / Social conditions; Manila (Philippines) / In popular culture; Manila (Philippines) / Politics and government; Politics and government; Social conditions; Philippines / Manila